STUDY OF 780 CASES OF INFERTILITY - Riaz, G. Sarwar; Saeed, Fauzia (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT Inspite of world population explosion, the desire for reproduction remains a basic human desire. Infertility is a complex phenomenon, and couples confronted with this problem, need a lot of emotional and psychological support besides intensive and prolonged investigations and treatment. Overall incidence of infertility varies from 15 to 20% all over the world. Etiological variation from one country to another is due to their differences in social background. A study of 780 cases of infertility have been carried out, to ascertain the cause of infertility. These patients range from 18 to 40 years of age, and come from various social groups. After initial investigations, they were divided into four groups, depending upon the etiological factor. It is observed that conception rate varied from one group to the other. Overall conception rate achieved was 44.743% which is reasonably encouraging with our present management.